Pelatihan Pembuatan Bahan Ajar Kimia Ramah Lingkungan dengan Pemanfaatan Limbah Rumah Tangga untuk Meningkatkan Kreativitas Siswa - Abdul Gani; Nasrullah; Irwan Yon Hadi; Sukranudin (Pendidikan Al-Gafari, 2024)
Sustainable chemistry education requires innovative approaches that connect learning materials to real-life contexts while fostering environmental awareness. One promising strategy is the utilization of household waste as a source of learning materials. This study aimed to develop a chemistry learning model based on household waste and to analyze its effects on students’ conceptual understanding, creativity, and environmental responsibility. The research employed a pre-test and post-test design with the same group. Quantitative data were obtained through conceptual understanding tests, while qualitative data were collected through classroom observations and in-depth interviews. Data analysis involved calculating the N-gain to measure learning improvement and interpreting qualitative findings for deeper insights. The results revealed a significant increase in students’ conceptual understanding, with average N-gain scores categorized as medium to high. Qualitative findings further indicated that students were more motivated, perceived the learning as contextual and meaningful, and demonstrated enhanced critical thinking skills and creativity. Integrating household waste into chemistry lessons proved relevant to the demands of 21st-century scientific literacy and showed potential to support sustainable education by promoting environmentally responsible attitudes. These findings highlight the importance of locally contextualized strategies in strengthening academic achievement while simultaneously shaping students’ character, suggesting broader adoption in chemistry education practices.